(untitled) (Seminar_BG, 2025)
This text examines the transformations of the conceptual border between an East Siberian post-industrial city and its surrounding nature through the lens of retired scientists and their work on various grant-funded projects aimed at protecting rare species and developing ecotourist infrastructure. By tracing the ways in which the scientists engage with the nature around their city, I show the change in value regimes, attitudes towards the environment, and the ways in which my interlocutors are trying to secure a niche in the green future of the city, which local and federal authorities have promised and committed to in a number of documents, and which local residents consider inevitable. References Abalakov, A. D., & Pankeyeva, N. S. (2010). Osobye ekonomisheskie zony turstko-rekreatsionnogo tipa Rossii: Sovremennyi etap razvitiia. Izvestiia Irkutskogo Gosudarstvennogo Universiteta, 3(2), 3–18. Ballestero, A. (2019). A Future History of Water. Durham: Duke University Press. https://doi.org/10.1215/9781478004516. Bokova, I. (2003). Chovekat, prirodata, muzeya [Human, nature, museum]. In: M. Elchinova and O. Todorov (eds.) Lovtsi na umove. Lektsii po antropologiya, v. 2. (pp. 18-24). Sofia: New Bulgarian University. Breyfogle, N. B. (2015). At the Watershed: 1958 and the Beginnings of Lake Baikal Environmentalism. The Slavonic and East European Review, 93(1), 147–180. https://doi.org/10.5699/slaveasteurorev2.93.1.0147. Castoriadis, C. (1987). The Imaginary Institution of Society. Boston: MIT Press. Creed, G. W. (1998). Domesticating Revolution: From Socialist Reform to Ambivalent Transition in a Bulgarian Village. Pittsburgh: Pennsylvania State University Press.. Decree of the Government of the Russian Federation № 1398-р/29.08.2014. (2014). Descola, P. (2014). Beyond Nature and Culture. Chicago: The University of Chicago Press. Ellison, S. H. (2018). Domesticating Democracy: The Politics of Conflict Resolution in Bolivia. Durham: Duke University Press. https://doi.org/10.1215/9780822371786. Gandy, M. (2006). Urban Nature and the Ecological Imaginary. In N. Heynen, M. Kaika, & E. Swyngedouw (еds.), In the Nature of Cities: Urban Political Ecology and the Politics of Urban Metabolism (pp. 62–72). London and New York: Routledge. Gandy, M. (2014). The Fabric of Space: Water, Modernity, and the Urban Imagination. Boston: The MIT Press. Garnizov, V. (2008) Ot ekologichen determinizam kam novi ekologii [From ecological determinism to new ecologies]. In: V. Garnizov and Ts. Lazova (eds) Lovtsi na umove. Lektsii po antropologiya, v. 3. (pp. 11-45). Sofia: New Bulgarian University. Georgiev, K. Forthcoming. Garazhniki: Gleaning, Trading, and Improvising in a Postindustrial Monotown. Graeber, D. (2001). Toward an Anthropological Theory of Value: The False Coin of Our Own Dreams. New York: Palgrave. Guentcheva, R. (2015). Napravi si sam muzei na sotsializma [DIY Museum of Socialism]. Seminar_BG, 8. https://seminar-bg.eu/spisanie-seminar-bg/broy8/561-napravi-si-sam-muzei-na-sotzializma.html [30.08.2025] Hemment, J. (2004). The Riddle of the Third Sector: Civil Society, International Aid, and NGOs in Russia. Anthropological Quarterly, 77(2), 215–241. https://doi.org/10.1353/anq.2004.0069. Hemment, J. (2007). Empowering Women in Russia: Activism, Aid, and NGOs. Indiana University Press. Hemment, J. (2012). Nashi, Youth Voluntarism, and Potemkin NGOs: Making Sense of Civil Society in Post-Soviet Russia. Slavic Review, 71(2), 234–260. https://doi.org/10.1017/S0037677900013607. Kochetkova, E. M. (2024). The Green Power of Socialism: Wood, Forest, and the Making of Soviet Industrially Embedded Ecology. Boston: The MIT Press. Kozhova, O. M. (1986). Nauka – proizvodstvu! Reshat v komplekse. Baykal’skiy tsellyuloznik, 17(467/30.04.1986), 3. Kopytoff, I. (1986). The Cultural Biography of Things: Commoditization as process. In A. Appadurai (ed.), The Social Life of Things (pp. 64–92). Cambridge: Cambridge University Press. https://doi.org/10.1017/CBO9780511819582.004. Lapin, B. F. (ed.). (1987). Slovo v zashchitu Baikala: Materlialy, diskusii [Words in defense of Baikal: Articles, discussions]. Irkutsk: Vostochno-Sibiskoe knizhnoe isdatel’stvo. Latour, B. (1994). We Have Never Been Modern. Harvard: Harvard University Press. MacPherson, C. B. (2011). The Political Theory of Possessive Individualism: Hobbes to Locke. Oxford: Oxford University Press. Marx, K. (1981 [1867]). Capital: A Critique of Political Economy (vol. 1). London: Penguin Books. Mikula, M. (2015). Vernacular Museum: Communal Bonding and Ritual Memory Transfer among Displaced Communities. International Journal of Heritage Studies, 21(8), 757–772. https://doi.org/10.1080/13527258.2015.1020961. Miller, D. (2008). The Uses of Value. Geoforum, 39(3), 1122–1132. https://doi.org/10.1016/j.geoforum.2006.03.009. Morris, J. (2016). Everyday Post-Socialism. London: Palgrave Macmillan. https://doi.org/10.1057/978-1-349-95089-8. Munn, N. D. (1992). The Fame of Gawa: A Symbolic Study of Value Transformation in a Massim (Papua New Guinea) Society. Durham: Duke University Press. Oldenburg, R. (1999). The Great Good Place: Cafés, Coffee Shops, Bookstores, Bars, Hair Salons, and Other Hangouts at the Heart of a Community. Philadelphia: Da Capo Press. Ostrovitianov, K. V., D. T. Shepilov, L. A. Leont’ev, I. D. Laptev, I. I. Kuz’munov & L. M. Gatovskii. (1954). Politicheskaia ekonomiia. Uchebnik. [Political Economy. A Textbook.] Moskva: Gossudarstvennoe isdatel’stvo politicheskoi literatury. Panfilov, O. (2014). Kul’t lichnosti Putina: put’ ot toptuna do diktatora. Krym.Realii. https://ru.krymr.com/a/26709735.html/ [20.11.2025] Roy, A. (2016). Public Power in the Age of Empire. In The End of Imagination (pp. 319–341). Chicago: Haymarket Books. Saunders, R. & Stukov, Vl. (2010). Historical Dictionary of the Russian Federation. Lanham: The Scarecrow Press. Seleyev, S., & Pavlov, A. (2016). Garazhniki. Moskva: Strana Oz. Smith, A. (2007 [1776]). An Inquiry into the Nature and Causes of the Wealth of Nations. Books I, II, III, IV and V. New York: MetaLibri. Snopek, K. (2015). Belyayevo Forever: A Soviet Microrayon on its way to the UNESCO List. Berlin: DOM publishers. Stoetzer, B. (2022). Ruderal City: Ecologies of Migration, Race, and Urban Nature in Berlin. Durham: Duke University Press. Strange, C. (2019). Monotown: Urban Dreams Brutal Imperatives. San Francisco: Applied Research and Design. Sundstrom, L. M. (2005). Foreign Assistance, International Norms, and NGO Development: Lessons from the Russian Campaign. International Organization, 59(2), 419–449. https://doi.org/10.1017/S0020818305050149. Szelényi, I. (2013). Poverty and Social Structure In Transitional Societies: The First Decade of Post-Communism. Sofia: Zhanet 45. Tsing, A. (2013). Sorting out Commodities: How Capitalist Value is Made through Gifts. HAU: Journal of Ethnographic Theory, 3(1), 21–43. https://doi.org/10.14318/hau3.1.003. Viveiros De Castro, E. (2012). Immanence and Fear: Stranger-Events and Subjects in Amazonia. HAU: Journal of Ethnographic Theory, 2(1), 27–43. https://doi.org/10.14318/hau2.1.003. Yurchak, A. (2005). Everything Was Forever, Until It Was No More: The Last Soviet Generation. Princeton: Princeton University Press. Zommer, E., & Zommer, E. (2016). Malenʹkii oazis bolʹshoi nauki: Istoriia Instituta ekologicheskoi toksikologii na Baikale [Small oasis for big science: History of the Institute for environmental toxicology at Baikal]. Irkutsk: Renome.